Reaching new solar heights: integrating high penetrations of PV into the power system. Issue 1 (21st November 2016) - Lew, Debra; Miller, Nicholas
Abstract : Installed capacity of solar photovoltaics (PV) continues to grow rapidly in the US. High penetrations and can create operational and reliability challenges. PV integration shares some attributes and mitigation strategies with wind, and differs in some key ways that will be discussed. This study investigates PV integration challenges and examines mitigation issues for utilities planning for high penetrations of PV, with a focus on the Western Interconnection of the US. System balancing becomes more difficult due to a duck‐shaped net load curve. Flexibility in the remaining generators, load, and the PV itself, is critical in balancing the system. Reliability impacts from PV have been studied less and addressed less than system balancing issues, but become more important at high penetrations. Understanding essential reliability services from PV, weak grid issues with PV, and distributed PV impacts on bulk power system reliability is critical for planning of high penetrations of PV.